Redesign of an Undergraduate Controls Laboratory with an Eye toward Accommodating Future Upgrades - Wieneke, Jacob; Schinstock, Dale; White, Warren N.; Hu, Guoqiang (Institute of Electrical and Electronics Engineers, 2010)
This paper describes a recent and very advantageous upgrade of the undergraduate controls laboratory in the Mechanical and Nuclear Engineering Department at Kansas State University. The current lab has been in use for about a decade. Details regarding the original hardware fundamental to the laboratory activities, including the embedded digital signal processor (DSP) and the brushless DC motor stand (called the “Motorlab”), are presented and a summary of each of the fourteen weekly lab exercises is included. The DSP control program and PC user interface (UI) were each written in C. In order to accommodate future lab needs and to ease the maintenance burden, the embedded DSP was replaced by a PC running Real-Time LabVIEW from National Instruments (NI) and a NI data acquisition card. The original lab software was replaced with programs produced graphically in LabVIEW, known as Virtual Instruments (VIs). The VIs implement the controller on the real-time PC as well as the user interface on a host PC. Both the embedded DSP and the LabVIEW controllers are able to close the loop on the laboratory equipment with a 10 kHz, hard real-time, sample rate.
Keywords: Control laboratory; Undergraduate education